Coronado's School of Quezon City Web Portal - Adorna, Ramon M.; Lagunero, Nathaniel S. ;Magda, Nicole John M. (Manila : National University, 2017)
Coronado's School of Quezon City We Portal has five (5) different users with different access levels: Administration (President), Teacher, Student, Librarian and Registrar. The Administrator (president/admin) can access this account. It can also add, delete, and edit the record of the students and the teachers and also the whole portal. The Teacher can upload/attach lesson and they can even create a quiz and post assignment. The Student can take the quiz through online and they can even download the past lesson that the teacher uploaded. The Student can view also their borrowed book from the library. They can also view their term and final term grade. The Librarian has the ability to view and check to know how many books borrow by the student. The librarian has the ability also to monitor and input the list of borrowed books. The Registrar is just for viewing and posting of term and final grades only.
Title page -- Recommendation for oral examination -- Approval Sheet -- Grammarian's certificate -- Dedication --Acknowledgement -- Executive Summary -- Table of contents -- List of figures -- List of tables -- Chapter 1. Introduction -- Chapter 2. Review of related literature and studies -- Chapter 3. Technical background -- Chapter 4. Methodology, Results and Discussion-- Chapter 5. Summary and Recommendation -- References -- Appendices
Research Method : Descriptive Method.
Includes bibliographical references.